Credit constraints and margins of import: First evidence for German manufacturing enterprises - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This study uses tailor made enterprise level data from various sources for firms from manufacturing industries to test for the link between credit constraints, measured by a credit rating score provided by a leading credit rating agency, and imports in Germany for the first time. We find empirical evidence that a better credit rating score is positively related to extensive margins of import - firms with a better score have a higher probability to import, they import more goods and they source from more countries of origin. The intensive margin of imports - the share of imports in total sales - is found not to be related to credit constraints.
Keywords: F14; 330; Credit constraints; imports; Germany